PATIENT LOYALTY IS INFLUENCED BY ELECTRONIC WORD OF MOUTH (E-WOM), SERVICE QUALITY AND PROMOTION AT THE SANUS AESTHETIC CLINIC - Rizki Aprilia; Hery Winoto Tj (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines the influence of Electronic Word of Mouth (eWOM), service quality, and promotion on patient loyalty at Sanus Aesthetic Clinic in Tangerang. Despite the clinic’s strategic location, patient numbers declined by 11% from 2023 to 2024, prompting an investigation into factors affecting loyalty. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) on survey data from 100 patients, the study tests three hypotheses. Results indicate that promotion significantly enhances patient loyalty, while eWOM and service quality show no statistically significant impact. The findings suggest that effective promotional strategies—such as discounts, referral programs, and value-added offers—play a crucial role in retaining patients, whereas online reviews and perceived service quality may not be decisive factors for loyalty in this context. These insights provide practical recommendations for aesthetic clinics to prioritize targeted promotions to sustain and grow their patient base.